Evaluation of the Feasibility of Temporary Waste Storage at the Integrated Laboratory Center, Syarif Hidayatullah State Islamic University Jakarta: Evaluasi Kelayakan Tempat Penyimpanan Sementara (TPS) Limbah di Pusat Laboratorium Terpadu (PLT), Universitas Islam Negeri Syarif Hidayatullah Jakarta - Dinda Rama Haribowo; Encep Dimyati; Syeiba Badra Uyunillah (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2022)
Temporary Waste Storage as place for storing waste in the Integrated Laboratory Center was established in 2019. This study aims to study and postpone the Temporary Waste Storage for waste from buildings and their management based on the Regulation of the Minister of Environment and Forestry Number 15 of 2020 and Number 19 of 2021 to make it a more appropriate and sufficient Temporary Waste Storage. The research method is carried out through a qualitative approach. Data collection techniques were carried out using field observation methods, data analysis using SWOT analysis through FGD. The results showed the amount of liquid waste stored was 753,799 liters and solid waste stored was 233.6 kg. The average temperature and humidity in the liquid waste storage room are 29.04°C and 68.47 RH% and in the solid waste storage room 29.17°C and 68.13 RH%. The temporary waste storage management system is in accordance with regulations and standards, the strategy resulting from the SWOT analysis is carried out by improving and adding facilities, as well as making a waste storage schedule to improve the quality of Temporary Waste Storage. Abstrak Tempat Penyimpanan Sementara (TPS) sebagai tempat menyimpan limbah di Pusat Laboratorium Terpadu (PLT) didirikan pada tahun 2019. Penelitian ini bertujuan untuk mengkaji dan mengevaluasi Tempat Penyimpanan Sementara (TPS) Limbah dari segi bangunan dan pengelolaannya berdasarkan Peraturan Menteri Lingkungan Hidup dan Kehutanan Nomor 12 tahun 2020 dan Nomor 19 tahun 2021 untuk terwujudnya TPS yang lebih layak dan mencukupi. Metode penelitian dilakukan melalui pendekatan kualitatif. Teknik pengumpulan data dilakukan menggunakan metode observasi lapangan, analisis data menggunakan analisis SWOT melalui FGD. Hasil penelitian menunjukkan jumlah limbah cair yang tersimpan 753,799 liter dan limbah padat yang tersimpan 233,6 kg. Besar rata-rata suhu dan kelembapan di ruang penyimpanan limbah cair 29,04°C dan 68,47 RH%, di ruang penyimpanan limbah padat 29,17°C dan 68,13 RH%. Sistem pengelolaan TPS limbah sudah sesuai regulasi dan standar, strategi hasil analisis SWOT dilakukan dengan memperbaiki dan menambahkan fasilitas, serta membuat jadwal pengangkutan dan pendataan limbah oleh petugas penyimpanan limbah agar meningkatkan kualitas TPS.